Prediction of the change in suitable growth area of Sabina tibetica on the Qinghai-Tibetan plateau using MaxEnt model - Li, Xiaoxiong; Yang, Dongsheng; Wang, Jingjie; Pan, Gang (Frontiers in Forests and Global Change, 2025)
As a keystone species maintaining alpine ecosystem stability, Tibetan juniper (Sabina tibetica) is endemic to the Qinghai-Tibetan Plateau, thriving at 2,800–4,600 m elevations. We employed the MaxEnt model with 10 bioclimatic and topographic variables to predict its distribution shifts under RCP4.5 and RCP8.5 scenarios for 2050 and 2070. Model performance was validated through five-fold spatial cross-validation (AUC = 0.932), utilizing 99 occurrence records from field surveys and biodiversity databases. Minimum winter temperature (35.1% contribution) and warmest quarter precipitation (18.9%) emerged as dominant drivers. The current suitable habitat (4.69 × 104 km2) is projected to decrease to 3.82 × 104 km2 (18.6% reduction) under RCP4.5-2050 and 2.78 × 104 km2 (40.7% reduction) by 2070. Under high-emission scenarios, suitable areas will contract to 3.83×10⁴ km² (RCP8.5-2050) and 3.86 × 104 km2 (RCP8.5-2070), showing 18.3% and 17.7% reductions respectively. Range contractions concentrate in western Sichuan and southeastern Tibet, with RCP4.5-2070 exhibiting the most severe habitat loss. with range contractions concentrated in western Sichuan and southeastern Tibet. Priority conservation areas were identified in the Yarlung Zangbo Valley and Hengduan Mountains. This study provides quantitative assessment of Sabina tibetica’s climate vulnerability, offering critical insights for adaptive management of high-altitude ecosystems under global change.